Places of silence, journeys of freedom : the fiction of Paule Marshall - DeLamotte, Eugenia C. (Penn studies in contemporary American fiction., 1998)
Places of Silence, Journeys of Freedom is the first study of Paule Marshall's work to focus explicitly on her contribution to feminism. It is also the first to identify one of her original contributions to narrative art - a technique of "superimposition" or "double exposure" through which her books have explored topics now at the heart of feminist debate